2019
DOI: 10.1186/s12864-018-5382-6
|View full text |Cite
|
Sign up to set email alerts
|

Genomic resources for the Neotropical tree genus Cedrela (Meliaceae) and its relatives

Abstract: BackgroundTree species in the genus Cedrela P. Browne are threatened by timber overexploitation across the Neotropics. Genetic identification of processed timber can be used to supplement wood anatomy to assist in the taxonomic and source validation of protected species and populations of Cedrela. However, few genetic resources exist that enable both species and source identification of Cedrela timber products. We developed several ‘omic resources including a leaf transcriptome, organelle genome (cpDNA), and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 83 publications
1
22
0
3
Order By: Relevance
“…Other recent studies have also demonstrated the efficacy of taxon-specific probe sets in resolving species-level relationships from herbarium DNA (Finch et al, 2019;Soto Gomez et al, 2019;White et al, 2019). Whereas Kadlec et al (2017) argued that high sequence variability across angiosperm orders precluded the usefulness of universal probes in resolving species-level relationships, Chau et al (2018) found that general purpose probes can be as effective as taxon-specific ones.…”
Section: Efficacy Of Universal Probesmentioning
confidence: 99%
“…Other recent studies have also demonstrated the efficacy of taxon-specific probe sets in resolving species-level relationships from herbarium DNA (Finch et al, 2019;Soto Gomez et al, 2019;White et al, 2019). Whereas Kadlec et al (2017) argued that high sequence variability across angiosperm orders precluded the usefulness of universal probes in resolving species-level relationships, Chau et al (2018) found that general purpose probes can be as effective as taxon-specific ones.…”
Section: Efficacy Of Universal Probesmentioning
confidence: 99%
“…S1) from Peru and surrounding countries. Hybridization capture probes were designed based on gene models of a C. odorata individual originating in Mexico as described in Finch et al (2019). Sequencing yield and depth were assessed using methods previously described (Finch 2018;Finch et al 2019) and included in the Supporting Information for this article (Appendix 1; Table S2) (Finch 2019a, b).…”
Section: Design Panel Sequencingmentioning
confidence: 99%
“…The increasing availability of genomic and transcriptomic data across the tree of life and the accessibility of pipelines to identify potential orthologs with low or single copy number ( Chamala et al., 2015 ; Faircloth, 2016 ) help support the design of clade-specific bait sets ( e.g. Vatanparast et al., 2018 ; Finch et al., 2019 ; Soto Gomez et al., 2019 ). Larridon et al.…”
Section: Introductionmentioning
confidence: 99%